Reproductive cycle of the sea cucumber Holothuria forskali (Holothuriida: Holothuriidae) in the Ría de Vigo (NW of Spain) - Ballesteros, Tania (2021)
Introduction: The exploitation of the sea cucumber (Holothuria (Panningothuria) forskali) in Ría de Vigo (NW Spain) is recent (2015) and it has been done until now with scarce or no information about some key biological aspects as reproduction, recruitment or growth. Objective: To describe the reproductive cycle of H. forskali in Ría de Vigo. Methods: We sampled fortnightly throughout 2018. We calculated gonadal condition indices (GCI) and gametogenic stages by classic histological methods. Results: The reproductive cycle of H. forskali in the Ría de Vigo is characterized by a sexual resting stage during spring, when temperature and daylight hours are lower; the beginning of gametogenesis during summer, when temperature is higher, daylight hours longer and the sea bottom is rich in nutrients; then, a period of spawns interspersed with a gonadal restoration during autumn and winter, when temperature is lower and food is scarce. Sex ratio is 1:1, however, the studied population is not synchronized, because females initiate maturation earlier. The comparison of the histological results with GCI indices suggest that GCI is a good indicator for gonadal stage. Fishery management strategies, such as a closure period, must be adapted to the reproductive stage. We recommend avoiding fishing between November and February to increase spawning potential ratio and, consequently, recruitment.